PENGEMBANGAN BUKU BELAJAR EJAAN BAHASA INDONESIA UNTUK SISWA SEKOLAH DASAR - Tria Selvi Lestari; Sripit Widiastuti; Ida Putriani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to develop a feasible Indonesian spelling textbook for elementary school students. This book is a kind of material and practice books. This research utilized Research and Development (R&D), and adopted Four-D development model consisting of four stages: (1) define, (2) design, (3) develop, and (4) disseminate. Due to the Covid-19 pandemic, the stages were simplified and terminated before the disseminate stage. The subjects of the readability test were 5 grade II teachers, and 5 grade II students at SDN Bendo 1 Blitar City. The data were collected through questionnaires, interviews, and documentation. The data were then analyzed by applying descriptive quantitative and qualitative method. The results revealed that the book was classified into feasible category. The book obtanined a percentage of 84.55% from the experts of materials and Bahasa Indonesian, and 83.75% from the experts of book design. Then, the result of readability test conducted to students obtained the percentage of 100% (very feasible). Then, the result of interviews conducted to students resulted in a positive response towards the textbook. Furthermore, the result of readability test conducted to teachers obtained the percentage of 100% (very feasible). Based on the interviews with the teachers, it was revealed that the book facilitated teachers in the writing process using correct Indonesian spelling.